Carbon Markets and Financial Mechanism for Sustainable Agriculture - Towards Net Zero Emissions - Anbumozhi, Venkatachalam; N , Balasubramani; A, Vincent (Journal of Agricultural Extension Management, 2022)
India is the world’s fourth-biggest emitter of carbon dioxide after China, the US and the EU. According to the FAO, agriculture, forestry, and other land-use practices account for 24% of global greenhouse gas emissions and agriculture alone accounts for 34% of global GHG emissions. In order to minimise GHG emissions from various sectors in general and agriculture in particular, various mechanisms are advocated by national and international organisations, among them carbon market is rapidly growing and engrossing the attention of development stakeholders. The carbon market is expected to grow by 10 - 40 billion dollars in 2030 with a higher carbon price. Several countries, including India, are committed to moving towards a net-zero emissions economy and adapting to low lowcarbon paths to economic growth and development. To achieve this, many Sustainable Agricultural Practices (SAPs) are promoted at farmer levels. Therefore, to understand various SAPs and the growing carbon market, the International Webinar on Carbon Finance for Agriculture towards Climate Risk Mitigation was organized on 20 January 2022 by the National Institute of Agricultural Extension Management (MANAGE). This article vividly discusses the major outcomes of the Webinar related to prevailing SAPs to minimise the GHG emission as well as various carbon financial mechanisms promoted globally